Respuesta :
Answer:
y-(-4)=-6(x-1)
its is either (x-1), or (x+1). Im not sure on the last part
Step-by-step explanation:
hope this helps :3
if it did pls mark brainliest
plug those numbers into y - y1 = a(x - x1)
so you would get y-(-4) = -6(x - 1) (this is your point-slope form)
simplify to get y + 4 = -6x + 6
simplify more to get y = -6x + 2
then 6x + y =2 (this is your standard form)
so you would get y-(-4) = -6(x - 1) (this is your point-slope form)
simplify to get y + 4 = -6x + 6
simplify more to get y = -6x + 2
then 6x + y =2 (this is your standard form)